2011
DOI: 10.1016/j.fishres.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A future for marine fisheries in Europe (Manifesto of the Association Française d’Halieumétrie)

Abstract: a b s t r a c tWe, members of the Association Franç aise d'Halieumétrie, share the conviction that European fisheries have a future. It is time to get off the wrong track. Radical change is required to embark on the path of sustainable development and truly implement the ecosystem approach to fisheries. Today, high fishing pressure is deployed to catch a rare resource, which in return is responsible for the rarity. We must reverse the situation: an abundant resource that affords high catches applying moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
(42 reference statements)
0
17
0
2
Order By: Relevance
“…Madagascar, located in the western Indian Ocean, one of the most important tuna fishing grounds in the world (in both volume and value of catches [21]), presents an interesting and highly relevant example for three reasons: (1) it was the first Indian Ocean country to sign, in 1986, a fishing agreement with the EU [22,23]; (2) it is the poorest country involved in such agreements with the EU [24]; and (3) it retains strong economic links with its former colonial ruler, France, one of the countries which benefits most from these fishing agreements, as evidenced by its large DWF present in most agreements.…”
Section: Madagascarmentioning
confidence: 99%
See 1 more Smart Citation
“…Madagascar, located in the western Indian Ocean, one of the most important tuna fishing grounds in the world (in both volume and value of catches [21]), presents an interesting and highly relevant example for three reasons: (1) it was the first Indian Ocean country to sign, in 1986, a fishing agreement with the EU [22,23]; (2) it is the poorest country involved in such agreements with the EU [24]; and (3) it retains strong economic links with its former colonial ruler, France, one of the countries which benefits most from these fishing agreements, as evidenced by its large DWF present in most agreements.…”
Section: Madagascarmentioning
confidence: 99%
“…Partly as a result of declining stocks in domestic waters and increasing global demand for seafood [2][3][4], the European Union (EU) has developed one of the largest DWFs in the world and has established foreign fishing agreements with twenty developing African-Caribbean-Pacific (ACP) countries 2 . Twelve of these agreements are specifically designed for the exploitation of tuna, while the others are ''mixed'' and also encompass shrimp and demersal fish species.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review revealed that the only possible way to achieve sustainability of the fishery sector is to include all affected parties [9,12,[36][37][38][39]. This DSC highlights the relevance of stakeholders by including experts representing four main stakeholder groups in the decision-making process by identifying and engaging them in the further execution of the DSC immediately after definition of the main goal.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is still a lack of appropriate structures to develop and get recognition for applied research and expertise at the interface between science, management and policy [37], this DSC presents an approach that overcomes this shortcoming. This DSC could provide a meaningful contribution for the means to better incorporate the human role and stakeholder role in achieving sustainability through economic viability and social fairness.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing a true EAFM was precisely at the core of the manifesto "A future for marine fisheries in Europe" published by the AFH in 2011 (Gascuel et al 2011). The EAFM calls for a change from traditional single species fisheries management to management that considers all implications and dimensions of fishery socio-ecosystems: multispecies catches, bycatches, trophic implications, habitat degradation, socio-economic issues, governance, etc More than ten years after its creation, the EAFM is progressively being implemented.…”
Section: On the Road To The Ecosystem Approach For Fisheries?mentioning
confidence: 99%